Hypertension and stroke in Asia: A comprehensive review from HOPE Asia - Turana, Yuda; Tengkawan, Jeslyn; Chia, Yook Chin; Nathaniel, Michael; Wang, Ji‐Guang; Sukonthasarn, Apichard; Chen, Chen‐Huan; Minh, Huynh Van; Buranakitjaroen, Peera; Shin, Jinho; Siddique, Saulat; Nailes, Jennifer M.; et al. (The journal of clinical hypertension (Greenwich, Conn.), 2021)
Stroke is the primary cause of disability and vascular death worldwide, including Asia. Asian characteristics that differ from the West lead to higher stroke incidence. Stroke epidemiology studies in Asia have shown varying levels of mortality, incidence, prevalence, and burden of disease. Hypertension is the most prevalent risk factor found in Asia. Besides ethnicity that is associated with stroke incidence, both systolic blood pressure, diastolic blood pressure, and blood pressure variability are positively correlated with stroke incidence. Post‐stroke cognitive impairment is one of the sequelae that affect one‐third of stroke survivors and has become a significant public health concern that is often neglected despite its increasing prevalence. Therefore, it is very important to prevent recurrence by treating stroke optimally and effectively. Increasing awareness and treatment adherence to hypertension, the leading risk factor for stroke, became the main goal in several countries in Asia.